2022
DOI: 10.3390/diagnostics12040880
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium—A More Important Role in CKD–MBD than We Thought

Abstract: Chronic kidney disease (CKD) is associated with different complications, including chronic kidney disease–mineral and bone disorder (CKD–MBD), which represents a systemic disorder that involves the presence of different mineral or bone structure abnormalities (i.e., modification of bone turnover, strength, volume, etc.), including even vascular calcification development. Even if, over the years, different pathophysiological theories have been developed to explain the onset and progression of CKD–MBD, the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 127 publications
0
7
0
Order By: Relevance
“…Therefore, it is important to manage the mineral metabolism to prevent VC [10]. Recent studies have reported that Mg plays an important role in VC pathogenesis and VC [21]. Hence, we focused on Mg, i-Ca, and VC levels in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to manage the mineral metabolism to prevent VC [10]. Recent studies have reported that Mg plays an important role in VC pathogenesis and VC [21]. Hence, we focused on Mg, i-Ca, and VC levels in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its impacts on hydroxyapatite and CPP formation, studies have shown that Mg also affects vascular calcification at the intracellular level [121,134]. As previously discussed, the transformation of VSMCs into an osteogenic phenotype is recognized as a significant contributor to the development and advancement of vascular calcification [135].…”
Section: Inhibitory Effects Of Mg On the Osteogenic Differentiation O...mentioning
confidence: 96%
“…Magnesium (Mg), the second most prevalent cation in cells after potassium, is involved in more than 300 enzymatic reactions and significantly impacts neurotransmitter release, oxidative stress prevention, bone metabolism, regulation of heart rhythm, and vascular tone ( 1 ). Mg ranges from 21 to 28 g in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…In CKD patients, serum Mg abnormalities have been found ( 1 ). CKD patients may have hypomagnesemia or hypermagnesemia ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation